The ESL/ELL teacher's survival guide : ready-to-use strategies, tools, and activities for teaching English language learners of all levels - Ferlazzo, Larry. (Jossey-Bass teacher, 2012)
"A much-needed resource for teaching English to all learnersThe number of English language learners in U.S. schools is projected to grow to twenty-five percent by 2025. Most teachers have English learners in their classrooms, from kindergarten through college. The ESL/ELL Teacher's Survival Guide offers educators practical strategies for setting up an ESL-friendly classroom, motivating and interacting with students, communicating with parents of English learners, and navigating the challenges inherent in teaching ESL students. Provides research-based instructional techniques which have proven effective with English learners at all proficiency levels Offers thematic units complete with reproducible forms and worksheets, sample lesson plans, and sample student assignments The book's ESL lessons connect to core standards and technology applications This hands-on resource will give all teachers at all levels the information they need to be effective ESL instructors"--